Minimally invasive Oxford unicompartmental knee arthroplasty ensures excellent functional outcome and high survivorship in the long term - Walker, Tilman; Hetto, Pit; Bruckner, Thomas; Gotterbarm, Tobias; Merle, Christian; Panzram, Benjamin; Innmann, Moritz Maximilian; Moradi, Babak (Knee surgery, sports traumatology, arthroscopy, 2019)
PURPOSE: Whether unicompartimental or total knee arthroplasty is superior for treatment of anteromedial knee osteoarthritis, is still uncertain. Therefore, the purpose of this study was to evaluate clinical and radiological outcome as well as long-term survivorship of medial Oxford unicompartmental knee arthroplasty (OUKA) at an independent center with a minimum follow-up of 10 years. - METHODS: This single-center retrospective cohort study reports the 10-15 years follow-up results of 113 consecutive patients (126 knees) after medial OUKA. Survivorship analysis was performed with several different endpoints and clinical outcome was measured using the Oxford Knee Score (OKS), American Knee Society Score (AKSS-O), range of motion (ROM), Tegner activity score and UCLA score. Radiological analysis was performed with focus on progression of arthritis in the lateral compartment. - RESULTS: A total of 16 patients (16 knees) underwent revision surgery resulting in a survival rate of 92.4% at 10 years and 88.6% at 15 years with the endpoint device-related revisions. The main reason for revision surgery was progression of arthritis in five patients (31.3%) followed by persistency of pain in three patients (18.7%). Clinical outcome was good to excellent with an OKS of 39.9 at 11 years, an AKSS-O of 89.3 and a mean range of motion of 122°. The radiological analysis revealed a significant progression of degenerative changes in the lateral compartment, however without any impact on the functional outcome. - CONCLUSION: Oxford UKA of the medial compartment ensures good long-term survivorship with an excellent functional outcome. Therefore, the results of this study support the continued use of OUKA in patients with anteromedial osteoarthritis. - LEVEL OF EVIDENCE: Retrospective cohort study, Level III.
Gesehen am 12.03.2020